(3ZGjI GdeCehd aj TQM hQbGJ GdCUhds - (3TgGH GdOjf GdQedi GdTGaYjs; (3GeGe GdMQejf , Qcf GdOjf CHh GdeYGdj,J (B478 (3g` s ((3efUhQ Hf bGSe GdHSGWi GdYeQi GdTGaYi GdMSjfi s)
(3ChdgG (B:s
(3CeG HYO agPG JYdjb Ydi cJGH GdhQbGJ ai CUhd Gdabg s
(3BNQgG (B:s
(3adh cGf cd eLJgO eUjHkG ef GdNWQ hGdEHGMI hGdUMI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3CUhd Gdabgs